Second Tumor Induction Risk in IMRT for Prostate Cancer: An Unbalanced Comparison Between Surgery and Radiotherapy?. Issue 6 (December 2015) - Calandrino, Riccardo; Perna, Lucia; Belli, Maria Luisa; Botti, Andrea; Cattaneo, Mauro; Fiorino, Claudio; Cozzarini, Cesare; Iori, Mauro
Abstract : Abstract: The aim of this study was to evaluate the risk of second tumor induction for prostate patients treated with volumetric modulated arc therapy in age classes 50–70. Based on both age-dependent models and doses to critical organs, the risk of second tumor induction was evaluated simulating the small field (prostate and seminal vesicles) and large field (whole pelvis) for Helical Tomotherapy and Rapid Arc. The doses to the organs closest to the treatment volume were derived from treatment planning system data. Whereas, due to the lack of calculation algorithms where leakage and internal radiation scattering are unreliable at a large distance from target, the doses to the organs outside the treatment volume were measured in an anthropomorphic phantom. Doses from Image Guided Radiotherapy (IGRT) were also assessed on phantom measurements. The Lifetime Attributable Risk (LAR) for second tumor induction increases from 2.2 to 13.7% as irradiated volume increases and age decreases. IGRT could add a non-negligible factor to the risk when daily set-up verification with high-resolution modality is included. As prostate cancer is detected earlier, the probability of an increase in early stage patients rises, and life expectancy thus increases. Radiotherapy has improved its capability in the tailoring of the dose around the target at the cost of a greater dose to surrounding organs, thus increasing the risk of second tumor induction, especially for those patients expected to survive 15 y or more.